Impact of previous percutaneous coronary intervention on cardiovascular outcomes and mortality after lung cancer surgery: A nationwide study in Korea - Dong Woog Yoon; Dong Wook Shin; Jong Ho Cho; Jong‐Hwan Lee; Jeong Hoon Yang; Kyungdo Han; Sang Hyun Park (Thoracic Cancer, 2020)
Background The number of patients with operable lung cancer with a history of percutaneous coronary intervention (PCI) has increased. However, cardiovascular outcomes and mortality, according to the time from PCI to surgery, and the follow‐up time after surgery are largely unknown. Here, we aimed to compare the cardiovascular outcomes and mortality of these patients with a history of PCI to those of patients without a history of PCI. Methods Using the Korean National Health Insurance Service Database, we selected 30 750 patients who underwent surgery for lung cancer between 2006 and 2014. Study outcome variables were all‐cause mortality, revascularization, intensive care unit (ICU) readmission, and stroke incidence. Patients were followed‐up until 2016. Results Of the 30 750 patients, 513 (1.7%) underwent PCI before surgery. The PCI group did not show an increased risk of death, ICU readmission, or stroke within one year of surgery, despite an increased risk of revascularization. However, one year after surgery, they showed a higher risk of death and revascularization than the non‐PCI group. The risk of revascularization was highest when the interval between PCI and surgery was <1 year and remained high when the interval was >3 years. Conclusions Patients who underwent PCI before surgery for lung cancer were at a higher risk of death than those in the non‐PCI group at one year after surgery. In addition, they showed higher short‐ and long‐term risks of revascularization than patients in the non‐PCI group. Careful long‐term management of cardiovascular risk is necessary for this population.